The Use of Voice Cues for Speaker Gender Recognition in Cochlear Implant Recipients. - Meister, Hartmut; Fürsen, Katrin; Streicher, Barbara; Lang-Roth, Ruth; Walger, Martin (Journal of Speech, Language & Hearing Research, 2016)
Purpose: The focus of this study was to examine the influence of fundamental frequency (F0) and vocal tract length (VTL) modifications on speaker gender recognition in cochlear implant (CI) recipients for different stimulus types. Method: Single words and sentences were manipulated using isolated or combined F0 and VTL cues. Using an 11-point rating scale, CI recipients and listeners with normal hearing rated the maleness/femaleness of the corresponding voice. Results: Speaker gender ratings for combined F0 and VTL modifications were similar across all stimulus types in both CI recipients and listeners with normal hearing, although the CI recipients showed a somewhat larger ambiguity. In contrast to listeners with normal hearing, F0-VTL and F0-only modifications revealed similar ratings in the CI recipients when using words as stimuli. However, when sentences were used, a difference was found between F0-VTL--based and F0-based ratings. Modifying VTL cues alone did not affect ratings in the CI group. Conclusions: Whereas speaker gender ratings by listeners with normal hearing relied on combined VTL and F0 cues, CI recipients made only limited use of VTL cues, which might be one reason behind problems with identifying the speaker on the basis of voice. However, use of the voice cues depended on stimulus type, with the greater information in sentences allowing a more detailed analysis than single words in both listener groups.